A Trust System for Broadcast Communications in SCADA (International Journal of Engineering and Computer Science, 2013)
Modern industrial facilities have command and control systems. These industrial command and control systems are commonly called supervisory control and data acquisition (SCADA). In the past, SCADA system has the closed operating environment, so this system was designed without security functionality. These days, as a demand for connecting the SCADA system to the open network increases, the study of SCADA system security is an issue. A key-management scheme is essential for secure SCADA communications. In this paper, ASKMA+TS which is a more efficient scheme that decreases the computational cost for multicast communication is introduced. ASKMA+TS reduce the number of keys to be stored in a remote terminal unit and provide multicast and broadcast communications. The last session discusses the use of a communications network security device, called a trust system, to enhance supervisory control and dataacquisition (SCADA) security. The major goal of the trust system is to increase security with minimal impact on existing utility communication systems.